EAACI guideline: Anaphylaxis (2021 update) - Muraro, Antonella; Worm, Margitta; Alviani, Cherry; Cardona, Victoria; Dunngalvin, Audrey; Garvey, Lene Heise; Riggioni, Carmen; de Silva, Debra; Angier, Elizabeth; Arasi, Stefania; Bellou, Abdelouahab; Beyer, Kirsten; et al. (Allergy (Copenhagen), 2022)
Anaphylaxis is a clinical emergency which all healthcare professionals need to be able to recognize and manage. The European Academy of Allergy and Clinical Immunology Anaphylaxis multidisciplinary Task Force has updated the 2014 guideline. The guideline was developed using the AGREE II framework and the GRADE approach. The evidence was systematically reviewed and recommendations were created by weighing up benefits and harms. The guideline was peer-reviewed by external experts and reviewed in a public consultation. The use of clinical criteria to identify anaphylaxis is suggested with blood sampling for the later measurement of tryptase. The prompt use of intramuscular adrenaline as first-line management is recommended with the availability of adrenaline autoinjectors to patients in the community. Pharmacokinetic data should be provided for adrenaline autoinjector devices. Structured, comprehensive training for people at risk of anaphylaxis is recommended. Simulation training and visual prompts for healthcare professionals are suggested to improve the management of anaphylaxis. It is suggested that school policies reflect anaphylaxis guidelines. The evidence for the management of anaphylaxis remains mostly at a very low level. There is an urgent need to prioritize clinical trials with the potential to improve the management of patients at risk of anaphylaxis.